Congenital Simple Hamartoma of Retinal Pigment Epithelium: Clinical and Imaging Findings - Mehmet Yasin Teke; Pinar Ç. Özdal; Figen Batioglu; Ufuk Elgin; Faruk Öztürk (Case Reports in Ophthalmological Medicine)
Congenital simple hamartoma of retinal pigment epithelium (CSHRPE) is a rare, asymptomatic, and incidentally detected benign lesion. However, it is very important to do the differential diagnosis from other pigmented retinal lesions. Its clinical presentation and imaging findings are very helpful in doing this differentiation. This paper presents clinical and imaging findings of a 56-year-old woman with incidentally detected CSHRPE. The lesion was small, heavily pigmented, well circumscribed, and slightly elevated. Optical coherence tomography (OCT) scanning was diagnostic and showed an elevated retina at the site of the lesion, increased optical reflectivity on its inner surface, optical shadowing of deeper structures, and clearly cut tumor margins. Ocular ultrasonography, fluorescein angiography, and fundus autofluorescence imaging which is firstly described in this report did not show any characteristic finding.